2015
DOI: 10.1080/0305764x.2014.988681
|View full text |Cite
|
Sign up to set email alerts
|

The effects of scientific representations on primary students’ development of scientific discourse and conceptual understandings during cooperative contemporary inquiry-science

Abstract: Teaching students to use and interpret representations in science is critically important if they are to become scientifically literate and learn how to communicate their understandings and learning in science. This study involved 248 students (119 boys and 129 girls) from 26 grade 6 teachers' classes in nine primary schools in Brisbane, Australia. Teachers were randomly allocated by school to one of three conditions: the contemporary science + representations condition (Experimental a ), the contemporary cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Professors to act more as facilitators and allow students to take greater responsibility for their own education and increase the levels of interactive education (Khorbortly & Budnik, 2014). It appears that as the children had more time to engage with the material, participate in cooperative peer discussions, and receive encouragement from their teachers to provide elaborated feedback to each other (Gillies, 2015), so that it could strengthen the employability skills of vocational teacher candidates (Stephenson & Sadler-McKnight, 2016;Rosenberg et al, 2012).…”
Section: Learning Implementationmentioning
confidence: 99%
“…Professors to act more as facilitators and allow students to take greater responsibility for their own education and increase the levels of interactive education (Khorbortly & Budnik, 2014). It appears that as the children had more time to engage with the material, participate in cooperative peer discussions, and receive encouragement from their teachers to provide elaborated feedback to each other (Gillies, 2015), so that it could strengthen the employability skills of vocational teacher candidates (Stephenson & Sadler-McKnight, 2016;Rosenberg et al, 2012).…”
Section: Learning Implementationmentioning
confidence: 99%
“…Research in Brisbane, Australia on 248 students from 26 Grade 6 classes in 9 elementary schools concluded that learning that directs the interpretation of science representation is essential when students want to reason scientifically. The students learn to communicate understanding in science (Gillies et al, 2015). A multiple representation approach (models, graphs, diagrams, text, etc.)…”
Section: Multiple Representation Approach In Elementary Schoolsmentioning
confidence: 99%
“…One approach to teaching inquiry that adopts a guided-inquiry approach is the 5Es model of inquiry instruction [22]. In this instructional model, students are provided with opportunities to participate in learning tasks that arouse their curiosity, challenge their conceptions or misconceptions, explore potential solutions, and re-organize and re-construct their current knowledge and understandings to develop explanations, based on the evidence they derive from their own investigations.…”
Section: Inquiry-based Sciencementioning
confidence: 99%